Fiscal sustainability assessment for Suriname 1978-2017: A fiscal reaction function approach - Albert Mungroo; Peggy Tjon Kie Sim-Balker (Inter-American Development Bank (IDB), 2020)
High and unsustainable public debt is an economic problem at the center of many emerging and developing economies. This paper investigates, for the period 1978-2017, how the Surinamese Government reacted to changes in public debt for the period 1978-2017 and assesses if fiscal policy was sustainable. To do so, a fiscal reaction function was estimated by using the following econometric techniques OLS, VAR, TAR, GMM and VECM. The results showed a positive and significant, but weak, relationship between the primary balance and total debt indicating that governments do react to debt-increases by improving the primary balance. The sustainability exercise also showed that fiscal policy is sustainable. However, it is found that this sustainability was not a result of appropriate fiscal policy. While factors outside of the Governments control worsened the primary balance through declining revenues, fiscal policy did not react swiftly by adjusting expenditures, which led to increases in inflation, affecting real interest rates, thus stabilizing debt in an unfavorable manner.
Keywords: B23; E62; H63; N96; 330; Primary balance; Output gap; Total debt; OLS; GMM; TAR; VAR; VECM